Holland Colours reports 8% sales growth in the first half of its fiscal year. Issue 12 (December 2018) - Unknown
Abstract : For the first half of its 2018/2019 fiscal year ended 30 September 2018, Dutch masterbatch specialist Holland Colours reported revenue of €45.6 million, up 8% from €42.4 million a year earlier despite a €0.8 million negative currency translation effect on the US dollar. The company's net income increased slightly from €3.33 million in the previous year to €3.37 million in the first half of fiscal 2018/2019.